Dewan Direksi, Komisaris Independen, Komite Audit dan Real Earnings Management - Abdurrahman, Rezi; Silalahi, Sem Paulus; Hanif, Rheny Afriana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This secondary research data is obtained from the IDX website and OSIRIS data set. The research model will be analyzed using the Ordinary Least Square (OLS) method. The results showed that DD financial expertise has a positive effect on REM, while the interaction of financial knowledge from KI and KA members weakens this positive effect. The purpose of this study is to examine the effect of Board of Directors (DD) expertise on real earnings management (REM). Then, this study also analyzes the effect of the expertise of the Independent Commissioner (KI) & Audit Committee (KA) on the relationship between board expertise and real earnings management. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) with observation years from 2014 - 2023.